IMPLEMENTASI INOVASI DAN KREATIVITAS MAHASISWA DALAM MEMPROMOSIKAN STIE APRIN DI ERA DIGITAL: IMPLEMENTASI INOVASI DAN KREATIVITAS MAHASISWA DALAM MEMPROMOSIKAN STIE APRIN DI ERA DIGITAL - Lani, Alfin; Saputra, Tedy Setiawan; Hershanty, Dessy; Jafrizal; Handayani, Cici; Sara, Yuni (Majalah Ilmiah Manajemen STIE Aprin Palembang, 2023)
Information technology in this era has become a common thing both among children, adolescents and even the elderly. The development of information technology in this era has an important role in carrying out an activity both in the Education, Work, and the scope of daily life. One form of the result of the development of technology and information is innovation and creativity, one of which is in media marketing. . Collaboration between technology and communication can be applied through one of the Instagram application media. The purpose of this study was to measure the influence of creativity and innovation on promotion. This study used quantitative methods involving 78 respondents in the STIE APRIN Palembang environment, research data was obtained by distributing a closed questionnaire through google form. The results showed that creativity and innovation affect promotion.